Brain metastases in patients with ovarian cancer. (3rd June 2022) - Limon, Dror; Shachar, Eliya; Wolf, Ido; Adar, Lyri; Peleg Hasson, Shira; Ferro, Leora; Safra, Tamar
Abstract: Background: Brain metastasis (BM) are uncommon among women with epithelial ovarian cancer (EOC). The frequency, risk factors and clinical repercussions of BM in these patients are not well described. Methods: We retrospectively evaluated EOC patients treated at our center from 2002 to 2020 and assessed their clinical parameters, risk for BM development and association with overall survival (OS). This cohort has a known high frequency of BRCA mutation carriers ( BRCAm ) due to women of Ashkenazi Jewish descent. Results: Among 1035 EOC patients, 29 (2.8%) were diagnosed with BM. The prevalence of BRCA mutations was more common among women with BM (56.5% vs. 34.3%, p  = 0.033). The BM rate in patients with BRCAm was higher than the BM rate in those with wildtype BRCA ( BRCAw ; 5.1% vs. 2.1%, OR = 2.6; 95% CI: 1.2–5.4, p  = 0.013). Median time from diagnosis to BM and from disease recurrence to BM was longer among patients with BRCAm . Median OS was not significantly different among patients with BM versus those without BM (59.4 vs. 73.4 months, p  = 0.243). After BM diagnosis, median OS was not statistically significantly different between patients with BRCAm and those with BRCAw (20.6 vs. 12.3 months, p  = 0.441). Treatment with poly (ADP-ribose) polymerase inhibitors and bevacizumab had no impact on subsequent development of BM. Conclusions: BM are rare among EOC patients. However, the risk is three-fold higher among patients with BRCAm . BM do not significantly alter OS among EOC patients. The higher rate of BM in patients with BRCAm may be related to longer OS in this subpopulation.